Delamination imaging in laminated composite plates using 2D wavelet analysis of guided wavefields. (20th November 2020) - Sha, Ganggang; Radzienski, Maciej; Soman, Rohan; Wandowski, Tomasz; Cao, Maosen; Ostachowicz, Wieslaw
Abstract: Delamination is a type of damage frequently occurring in laminated composite plates. Delamination detection is crucial to ensure structural integrity and safety. This paper presents a delamination imaging algorithm based on the space-wavenumber analysis of guided wavefields using two-dimensional (2D) continuous wavelet transform (CWT). The premise of this algorithm is that delaminations in a structure will alter wavenumbers in the delamination regions. The state of the art uses the short-space Fourier transform (SSFT) for local wavenumber analysis in order to capture these wavenumber alterations. However, window size in local wavenumber analysis using SSFT needs to be determined according to the wavelength in the delamination regions, which is not known a priori. Moreover, window size in SSFT is fixed and cannot adapt to the wavenumber alterations in varying damage scenarios. To address these disadvantages, the 2D CWT is introduced to analyze the guided wavefield data in the space-wavenumber domain leading to 2D CWT-wavefields. The wavenumber alterations induced by delaminations are well isolated in the 2D CWT-wavefields at fine scales. Window size in wavelet analysis is flexibly adapted to guided wavefields from varying damage cases by adjusting wavelet scale factor that is seen as the pseudo-wavenumber. A final damage map is developed by fusing the 2D CWT-wavefield images. The algorithm is successfully used in detecting multiple delaminations in a GFRP plate with the accurate location, size, and shape of each delamination clearly visualized in the final damage map.